The effects of a high carbohydrate diet on cortisol and salivary immunoglobulin A (s-lgA) during a period of "overtraining" amongst Olympic and Iron Man triathletes - Costa, R. J.; Jones, G. E.; Coleman, R.; Lamb, K. L.; Williams, J. H. H. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
Investigations into the mechanisms by which exercise affects immune function suggest links to a number of factors including the stress hormone cortisol and s-IgA (Gleeson et al, 2004). Extended periods of elevated cortisol have been shown to produce a chronic immunosuppressive state, as observed in endurance athletes after prolonged exercise bouts. Subsequently, decreases in salivary IgA have been correlated with an increase in the incidence of upper respiratory tract infection (URTI). Recent nutritional manipulations have been shown to attenuate the immunosuppressive effects of excessive exercise. However, the most impressive results have been seen in carbohydrate feedings on immune and endocrine maintenance. Carbohydrate feeding during exercise has been shown to modify the immune responses by reducing the secretion of cortisol (Bacurau et al. 2002). However, studies on the effects of a prescribed high carbohydrate diet on immune function during exercise have been few, and it remains to be investigated whether a such a diet diminishes the immunosuppressive responses following consecutive days of excessive strenuous endurance exercise (`over-training`). Therefore, the aim of this study was to observe the effects of a 6-day high carbohydrate (H-CHO) diet on the responses of the immunosuppressive stress hormone cortisol and salivary immunoglobulin A (s-IgA) during a period of over-training by endurance athletes. Methods Thirty-two males (mean ± SD: age 32.1 ± 9 yr; VO2max 69.9 ± 6.5 mL·kg-1·min-1 estimated body fat 12.1 ± 5.7 %), competitively trained in Olympic and Iron Man distance triathlons were randomly allocated into a self-selected (SS) diet group or a H-CHO (12g CHO kgbm-1·day-1) group. All subjects performed a 1 hour running exercise bout at 70% VO2max per day, for six consecutive days in addition to their usual training regimes. On three of these days (1, 4 and 6) the 1 hour extra exercise was conducted in a laboratory on a motorised treadmill. On these days, samples of saliva were taken via a dribble method pre, immediately post, and morning post-exercise bout. The concentrations of s-IgA and cortisol were determined by sandwich ELISA and indirect competitive ELISA, respectively. Blood glucose levels (pre and post exercise) were measured from finger-prick samples via an Accutrend monitor). Results A 3-way (Group x Day x Time) mixed model ANOVA revealed a significant (P< 0.001) interaction effect of Group x Time on cortisol (Fig. 1), with a marked increase in concentrations occurring in the SS diet group pre to post intervention and pre to morning afterwards (P< 0.01), compared to a non-significant decreasing trend in the H-CHO group. Conversely, for s-IgA, a significant (P = 0.009) Group x Time interaction (Fig. 2) reflected higher post exercise s-IgA concentrations (P< 0.005) than pre exercise in the H-CHO diet group, and a non-significant decreasing trend in the SS diet group. Blood glucose levels were found to decrease pre to post exercise significantly in the SS diet group (P< 0.01), whilst remaining stable in the H-CHO group. Discussion/Conclusion These data demonstrate that the consumption of a high CHO diet over a 6 day period of over-training has a favourable effect on markers of immune activity. These acute effects of additional strenuous exercise (elevated s-IgA and suppressed cortisol response) suggest a reduced risk of URTI compared to those athletes consuming a self-selected diet. In addition, that such a diet was sufficient to ensure the maintenance of blood glucose concentration during the bouts of over-training, can only be beneficial in terms of the athletes` exercise capacity and performance.